Sex Differences Dictate the Movement Patterns of Striped Hyenas, Hyaena hyaena, in a Human-Dominated Landscape - Bar-Ziv, Einat; Picardi, Simona; Kaplan, Asaf; Avgar, Tal; Berger-Tal, Oded (Frontiers in Ecology and Evolution, 2022)
Large-carnivore populations have experienced significant declines in the past centuries in extended parts of the world. Habitat loss, fragmentation, and depletion of natural resources are some of the main causes of this decline. Consequently, behavioral flexibility, enabling the exploitation of anthropogenic food resources in highly disturbed human-dominated landscapes, is becoming critical for the survival of large carnivores. These behavioral changes increase the potential for human-large carnivore conflict and can further intensify carnivore persecution. Here, we examine how land cover types (representing a gradient of anthropogenic disturbance) alter the behavior of striped hyenas (Hyaena hyaena) in a human-dominated landscape in Israel, and whether differences in life history between males and females affect their reaction to such disturbances and consequently their level of exposure to humans. We used a Hidden Markov Model on GPS-tracking data for seven striped hyenas to segment individual-night trajectories into behavioral states (resting, searching, and traveling). We then used multinomial logistic regression to model hyenas' behavioral state as a function of the interaction between land cover and sex. Females traveled less than males both in terms of average distance traveled per hour, per night, and nightly net displacement. Most steps were classified as “searching” for females and as “traveling” for males. Female hyenas spent a higher proportion of time in human-dominated areas and a lower proportion in natural areas compared to males, and they were also more likely to be found close to settlements than males. Females changed their time allocation between natural and human-dominated areas, spending more time resting than traveling in natural areas but not in human-dominated ones; males spent more time searching than resting in human-dominated areas but were equally likely to rest or search in natural ones. The differences in life history between male and female hyenas may reflect different motivations for space use as a means to optimize fitness, which affects their exposure to humans and therefore their potential involvement in human-hyenas conflict. Understanding the mechanisms that lead to behavioral change in response to human disturbance is important for adaptive management and promoting human large-carnivores co-existence in general.